2014
DOI: 10.1016/j.cyto.2013.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional responses of neonatal mouse lung to hyperoxia by Nrf2 status

Abstract: Hyperoxia exposure can inhibit alveolar growth in the neonatal lung through induction of p21/ p53 pathways and is a risk factor for the development of bronchopulmonary dysplasia (BPD) in preterm infants. We previously found that activation of nuclear factor erythroid 2 p45-related factor (Nrf2) improved survival in neonatal mice exposed to hyperoxia likely due to increased expression of anti-oxidant response genes. It is not known however, whether hyperoxic induced Nrf2 activation attenuates the growth impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…GDF15 is expressed and induced in response to hypoxia in human pulmonary vascular endothelial cells (Nickel et al, 2011). It is also induced in animal models of lung injury in both adult and neonatal mice (Bhattacharya et al, 2012; Lingappan et al, 2014; McGrath-Morrow et al, 2014; Zimmers et al, 2005). We have previously shown that GDF15 is induced in pulmonary epithelial (BEAS-2B) and endothelial (HPMEC) cells upon exposure to hyperoxia (Tiwari et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…GDF15 is expressed and induced in response to hypoxia in human pulmonary vascular endothelial cells (Nickel et al, 2011). It is also induced in animal models of lung injury in both adult and neonatal mice (Bhattacharya et al, 2012; Lingappan et al, 2014; McGrath-Morrow et al, 2014; Zimmers et al, 2005). We have previously shown that GDF15 is induced in pulmonary epithelial (BEAS-2B) and endothelial (HPMEC) cells upon exposure to hyperoxia (Tiwari et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed and induced in response to hypoxia in human pulmonary vascular endothelial cells and treatment with recombinant human GDF15 decreased apoptosis and improved cellular proliferation. GDF15 is induced in animal models of lung injury (McGrath-Morrow et al, 2014; Zimmers et al, 2005). We have shown that GDF15 was among the top five genes induced in the murine lungs in vivo when subjected to hyperoxia (Lingappan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown in a variety of disease models that pharmacologic activation of Nrf2 can reduce inflammation and oxidative stress, which are hallmark features of PTB. Additionally, prenatal treatment with sulforaphane, an Nrf2 activator21, showed beneficial effects in mouse models of postnatal hyperoxia58 and epidermolysis bullosa simplex59. Thus, Nrf2 activators, such as sulforaphane, may represent a promising strategy to reduce PTB.…”
Section: Discussionmentioning
confidence: 99%